Pengaruh Dana Bos Terhadap Motivasi Belajar Siswa SD Se-Kecamatan Kotamobagu Timur Kota Kotamobagu - Margareta O. Sumilat (Peneliti.net, 2022)
The purpose of this study was to obtain the results of the analysis and description of the effect of School Operational Assistance funds on the learning motivation of elementary school students in the East Kotamobagu District, Kotamobagu City, and the magnitude of the effect of the School Operational Assistance fund on the learning motivation of elementary school students in East Kotamobagu District, Kotamobagu City. Kotamobagu.This study uses a quantitative research approach, which uses data that can be calculated to produce a strong quantitative interpretation. So quantitative data is the value of changes that can be expressed in the form of numbers (statistics). The existence of financing through the School Operational Assistance Fund program has had a significant influence on the Learning Motivation of Elementary School Students in East Kotamobagu. The financing of the School Operational Assistance Fund is only required for non-personnel financing. Learning Motivation of Elementary School Students in East Kotamobagu is still influenced by other factors that were not studied but have a significant influence, which is 46.3%